Annie - Huston, John, 1906-1987.; Stark, Ray.; Sobieski, Carol; Finney, Albert, 1936-; Burnett, Carol; Peters, Bernadette; Reinking, Ann.; Curry, Tim.; Quinn, Aileen; Strouse, Charles; Columbia Pictures; Columbia TriStar Home Video (Firm) (Culver City, Calif. : Columbia TriStar Home Video, 2003)
The story of the comic strip character Little Orphan Annie, who is adopted by billionaire "Daddy" Warbucks.
Full screen format (1.33:1).
Originally released as a motion picture in 1981.
Based on the stage play by Charles Strouse, which was based on the comic strip Little Orphan Annie, created by Harold Gray.
Special features include: Age of Annie Trivia Game ; theatrical trailers ; interactive menus ; scene selections.
Choreography, Arlene Phillips ; director of photography, Richard Moore ; production design, Dale Hennesy ; Margaret Booth, editor ; Charles Strouse, music ; Martin Charnin, lyrics ; Ralph Burns, music arranger/conductor.
Albert Finney, Carol Burnett, Bernadette Peters, Ann Reinking, Tim Curry, Geoffrey Holder, Edward Herrmann, Aileen Quinn.
Keywords: Little Orphan Annie (Fictitious character) -- Drama; Orphans -- United States -- Drama; United States -- Social life and customs -- 1918-1945 -- Drama; Feature films; Films for the hearing impaired; Musical films